(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines the role of interdisciplinary integration in enhancing learners’ communicative competence within the context of foreign language education. As modern educational systems shift toward holistic and competency-based approaches, interdisciplinary instruction has gained substantial importance for fostering meaningful, authentic, and socially grounded language use. The study discusses theoretical foundations of communicative competence, explores models of interdisciplinary integration, and explains how cross-disciplinary knowledge and real-world tasks contribute to linguistic, sociolinguistic, strategic, and discourse competence. Special attention is given to the benefits of content-based learning, project-based learning, and CLIL (Content and Language Integrated Learning), as well as the challenges educators face in designing interdisciplinary curricula. The article concludes by emphasizing the need for pedagogical collaboration, curriculum redesign, and teacher training to ensure successful interdisciplinary integration.